The presence of ovarian endometrioma adversely affect ovarian reserve and response to stimulation but not oocyte quality or IVF/ICSI outcomes: a retrospective cohort study - Cheng Zeng; Ruihui Lu; Xin Li; Yanrong Kuai; Sheng Wang; Qing Xue (BMC, 2022)
Abstract Background The possible impact of ovarian endometriomas (OMAs) on in vitro fertilization (IVF) outcomes remains controversial. Therefore, this study aimed to assess the impact of OMAs on IVF cycle parameters, including ovarian reserve and response to stimulation, embryo quality and pregnancy outcomes. Methods This retrospective cohort study included 2067 patients undergoing their first IVF/ICSI cycles between January 2018 and December 2020. The study group included 154 infertile women who had OMAs. The control group consisted of 1913 women without endometriosis, and finally 305 women were matched according to maternal age, body mass index (BMI), and infertility duration by propensity score matching (PSM). Cumulative live birth rate (CLBR) was set as the primary outcome measure. Logistic regression analysis was conducted on the basis of clinical covariates assessed for their association with CLBRs. Subgroup analyses were performed to evaluate the effect of ovarian surgery, cyst size and laterality on CLBRs. Results Women with OMAs had significantly lower ovarian reserve markers (AMH and AFC), number of follicles, oocytes, embryos, and top-quality embryos than women in the control group (p < 0.05). However, the CLBRs were comparable between the two groups (55.64% versus 54.34%, p = 0.806), regardless of previous history of ovarian surgery. Multivariate analysis revealed association between age (OR = 0.861; 95% CI [0.806-0.921]; p = 0.000), top-quality embryos (OR = 1.829; 95% CI [1.526-2.193]; p = 0.000) and the CLBRs. A negative correlation between OMA size and AFC levels in patients with unoperated OMAs was detected (r = -0.264, p = 0.007). Meanwhile, significant decrease in ovarian reserve with lower AFC, fewer oocytes, embryos and top-quality embryos were observed in patients with OMAs size ≥ 6 cm (p < 0.05). Moreover, ovaries with OMAs had a significantly lower AFC (P = 0.006) but similar number of oocytes when compared with contralateral ovaries without OMAs. Conclusion Infertile women with OMAs were implicated in considerable decreases in ovarian reserve and response to stimulation, but no apparent adverse effects on oocyte quality or clinical outcomes. OMAs surgery and OMAs size may adversely affect ovarian reserve, but not CLBR.